RE-DESIGN UI/UX WEBSITE JAHITKU MENGGUNAKAN METODE DESIGN THINKING - phoa, raygina; Thayf, Mohammad Sofyan S.; Pontoh, Zaenab (STMIK KHARISMA Makassar, 2025)
The fashion and garment industry is growing rapidly, making individuals' needs for appropriate clothing continue to increase. Jahitku is a web-based platform created so that tailors can reach more customers, provide good service, and customers get information according to their needs at affordable prices and high quality. However, Jahitku has problems in optimizing the relevant website, inconsistent layout, button navigation that doesn't work, and using colors that lack contrast. The aim of this research is to redesign the Jahitku website to achieve better user satisfaction. In this research, by applying the Design Thinking method, existing functions are analyzed and their usefulness is tested on the System Usability Scale (SUS). Making a prototype using the Design Thinking method produced significant recommendations through SUS testing, resulting in a final test score of 78.775. This score has increased compared to the previous score of 48.125 which was still in the low category. This improvement shows a significant improvement in user experience from “Poor” to “Good”. Thus, it can be concluded that by updating the appearance of the Jahitku website, the user experience can be improved and the Jahitku website can become more effective and attractive to users.